Analisis Praktik Klinik Keperawatan Pada Pasien CKD (Chronic Kidney Disease) Dengan Intervensi Inovasi Sipping Ice Cube Therapy Terhadap Penurunan Rasa Haus Di Ruang Perawatan Rsud. Prof. DR. H. Aloei Saboe Kota Gorontalo - Fadli Syamsuddin; Iskandar Simbala; Hendra Radjulani (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Chronic Kidney Disease (CKD) This is a gradual and irreversible kidney disorder that affects the body's capacity to regulate metabolism, fluids, and electrolytes, leading to the development of uremia. Hemodialysis (HD) patients with chronic renal failure are subject to fluid, dietary and pharmaceutical restrictions as well as activity and medication limits. Weight gain, edema, and high blood pressure will occur if fluid balance is not maintained or if there is excess fluid between dialysis sessions. But limiting fluids while receiving hemodialysis can have a number of negative consequences on the body, one of which is thirst and dry mouth (xerostomia), caused by decreased salivary gland production. This scientific study uses a descriptive methodology along with nursing care strategies to apply the "sipping ice cubes therapy" strategy to reduce thirst in CKD patients receiving hemodialysis. Evidence-based practice of nursing This procedure is carried out in the Nursing Room of RSUD Dr. dr. Aloei Saboe Gorontalo City on December 26 2022 and January 26 2023. According to researchers, the administration of the innovative therapy "Sipping Ice Cubes Therapy" can significantly reduce thirst levels in CKD (Chronic Kidney Disease) patients. It can be seen from the 6 respondents who were given the innovative therapy "sipping ice Cubes Therapy" all of which gave a positive response after evaluation, both direct evaluation after giving therapy or evaluation after 3 days of giving the implementation of "sipping ice Cubes Therapy"